Distribution of hemoglobinopathies in patients presenting for electrophoresis and comparison of result with High performance liquid chromatography (Journal of Pathology of Nepal, 2015)
Background: Nearly 226 million carriers of thalassemias and abnormal hemoglobin are present worldwide according to the World Health Organization (WHO). The laboratory plays an important role in the investigation of the thalassemias and hemoglobinopathies. Cellulose acetate electrophoresis at alkaline pH and diagnosis based mainly on visual impression of thickness of band may miss the thalassemic trait patients. The aim of this study was to find out different hemoglobinopathies and thalassemia presenting in our hospital and to compare electrophoresis results with HPLC.Materials and Methods: This study was performed in the hematopathology section of Department of Pathology of Tribhuvan University Teaching Hospital on cases sent for electrophoresis during 18 months period from October 2013 to March 2015 and included hemoglobinopathies and thalassemias identified by either electrophoresis or HPLC. 97 cases fulfilled the inclusion criteria and thus were included in the study. Electrophoresis at alkaline pH was done in all whereas HPLC was performed in 27 cases.Results: A sharp peak of hemoglobinopathies and thalassemias was seen in Tharu community though other communities are also affected. Thalassemia trait was the most common diagnosis (26.8%) followed by sickle cell anemia (21.6%).  Electrophoresis was efficient in detecting some alpha thalassemia variants but missed many cases of beta thalassemia trait.Conclusion: Beta Thalassemia trait and sickle cell anemia both are common in Nepal , along with some other hemoglobinopathies  A sharp peak of hemoglobinopathies and thalassemias are seen in Tharu community. These abnormal hemoglobins and thalassemias are mainly seen in Terai region. Electrophoresis fails to quantify hemoglobin percentage and thus is not appropriate test in beta thalassemia screening.